Money as a coordinating device of a commodity economy: old and new, Russian and French readings of Marx - Nikolay Nenovsky (Revue de la Régulation)
We focus on some original approaches so as to find a solution to the “coordination problem” of the decentralised commodity economy in the different interpretations (and refutations) of Marx, stressing the central role of money. We reconstruct in a comparative perspective the approaches of two contemporary French scholars, Jean Cartelier and André Orléan and of two Russian economists, Isaak Rubin and Peter Struve who worked in the beginning of the last century. Our reconstruction starts with Marx although other approaches are also possible. Each of the four scholars under review offered his own methods of solving the issue of coordination. Although the ideas of the four authors intertwined, we can differentiate between two pairs namely Rubin/Orléan (part 1) and Struve/Cartelier (part 2). This corresponds to the radicality of their analytical solutions. While the former pair upheld the theory of value (each one in his own way), the latter actually eliminated it (again each one in his own way).